Pengembangan Nilai-Nilai Demokratis Mahasiswa Melalui Pendidikan Kewarganegaraan - Rexi Pandri; Eva Damayanti; Metri Afriani; Rahmi Putri Pratama; Nurhayati Nurhayati; Juneti Juneti; Angga Karomi (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of the study was to determine the value of student democracy through civic education. This research method was conducted using a descriptive method with a qualitative approach. The results of the study show that students must always implement democratic values, so that their role as agents of change in society can be more optimal. Today's democratic values ​​can be instilled from an early age through mutual respect for one another. The objectives of Citizenship Education include: 1) Thinking critically about Citizenship issues; 2) Participate in the life of society, nation and state; 3) Develop positively and democratically; 4) Interact with other nations. The conclusion of the study is that Citizenship Education is a subject with a focus on self-formation that is diverse in terms of religion, socio-cultural, language, age, and ethnicity to become intelligent, skilled, and characterized Indonesian citizens based on Pancasila and the 1945 Constitution. Keywords: Citizenship Education, Democratic Values, Students